The development of efficient hemi-autotrophic carbon fixation in Escherichia Coli - Hendriks, Rudolf Martinus Antonius (2023)
Carbon fixation is a process vital to any life and as by far its most prevalent variant, the Calvin Benson Bassham (CBB) cycle is vital to virtually all known terrestrial life. Mostly occurring in plants, it uses light energy to sequester atmospheric carbon dioxide (CO2) and convert it into biomass. As the most inefficient natural carboxylation process and source of most biomass documented, even a small increase of its performance could have vast downstream effects. Such a development could assimilate the abundantly available atmospheric CO2 while generating minimal amounts of waste for any biosynthesized product. The Escherichia coli bacterium was previously shown to functionally express the CBB cycle upon the addition of phosphoribulokinase (PRK) and ribulose 1,5-bisphosphate carboxylase/oxygenase (RuBisCO). Further knock-outs severed its energetic metabolism from the carbon metabolism resulted CO2-dependent biomass accumulation. This carbon fixation is driven by the energy independently generated in the TCA cycle from a supply of pyruvate. This unique, split metabolism was dubbed hemi-autotrophy.